Tumor necrosis factor-α and osterix expression after the transplantation of a hydroxyapatite scaffold from crab shell (Portunus pelagicus) in the post-extraction socket of Cavia cobaya - Irvan Salim; Michael Josef Kridanto Kamadjaja; Agus Dahlan (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2022)
Background: Socket preservation using bone graft is one way to minimise resorption and maximise the bone formation process. Tumor necrosis factor-α (TNF-α) is an inflammatory cytokine that affects bone regenerating osteoblast activity, while osterix (Osx) is an osteoblast-specific transcription factor that activates gene receptors during pre-osteoblast differentiation. The hydroxyapatite (HA) scaffold from crab shells (Portunus pelagicus) has osteoconduction properties. Purpose: To analyse the decrease of TNF-α expression and the increase of Osx expression and the correlation between these two in the post-extraction socket after the transplantation of a crab shell HA scaffold. Methods: The lower left incisors of Cavia cobaya (n = 24) were extracted and divided into four groups: the first and second groups were control groups on Day 7 and Day 14 (K7 and K14), the third and fourth groups were treatment groups (P7 and P14). The statistical analysis used was a multivariate analysis of variance (MANOVA) with a significance level of 0.05. Results: A MANOVA test showed that the use of crab shell HA scaffolds led to a significant difference (p < 0.05) in TNF-α expression (p = 0.01) and Osx expression (p = 0.01). A Pearson correlation test result showed a strong inverse correlation between TNF-α and Osx expressions (p = 0.00 and r = -0.78). Conclusion: The transplantation of HA scaffolds from crab shells can decrease TNF-α expression but increase Osx expression in the post-extraction socket of C. cobayas. Furthermore, an inverse correlation was found between TNF-α and Osx.